The cross-sectional dynamics of German business cycles: a bird's eye view - Jörg Döpke; Michael Funke; Sean Holly; Sebastian Weber (Deutsche Bundesbank, 2005)
We establish some stylised facts for Germany's business cycle at the level of the firm. Based on longitudinal firm-level data from the Bundesbank's balance sheet statistic covering, on average, 55,000 firms per year from 1971 to 1998, we analyse the reallocation across individual producers and, in turn, the connection of this reallocation to aggregate business cycles. The empirical results indicate a pronounced heterogeneity of real sale changes across firms. Moreover, the distribution of growth rates of firm's real sales is influenced by business cycle conditions. In particular, the cross-section skewness of real sales changes is strongly counter-cyclical. The results confirm most of the findings for the UK and the US by Higson et al. (2002, 2004) and are, therefore, robust stylised facts of the business cycle.
Keywords: D21; E32; D92; 330; business cycles; cross-sectional moments; firm growth; Konjunktur; Umsatz; Unternehmensentwicklung; Schätzung; Deutschland